2021
DOI: 10.3390/nu13010181
|View full text |Cite
|
Sign up to set email alerts
|

Gynura procumbens Root Extract Ameliorates Ischemia-Induced Neuronal Damage in the Hippocampal CA1 Region by Reducing Neuroinflammation

Abstract: Gynura procumbens has been used in Southeast Asia for the treatment of hypertension, hyperglycemia, and skin problems induced by ultraviolet irradiation. Although considerable studies have reported the biological properties of Gynura procumbens root extract (GPE-R), there are no studies on the effects of GPE-R in brain damages, for example following brain ischemia. In the present study, we screened the neuroprotective effects of GPE-R against ischemic damage and neuroinflammation in the hippocampus based on be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…In addition, CVE treatment significantly reduced the ischemia-induced apoptosis and increased anti-apoptotic protein, consistent with in vitro study. To elucidate the possible mechanisms against ischemic damage in the gerbil hippocampus, we focused on oxidative stress and inflammatory responses in the hippocampus after ischemia, because several studies have demonstrated that CVE has anti-inflammatory activity [28,40], and inflammation is one of the main pathways for neuronal death after ischemia in the gerbil hippocampus [41,42]. Overexpression of ROS induced by ischemia/reperfusion causes lipid peroxidation of polyunsaturated fatty acids in the neuronal membrane and disrupts the cell membrane [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CVE treatment significantly reduced the ischemia-induced apoptosis and increased anti-apoptotic protein, consistent with in vitro study. To elucidate the possible mechanisms against ischemic damage in the gerbil hippocampus, we focused on oxidative stress and inflammatory responses in the hippocampus after ischemia, because several studies have demonstrated that CVE has anti-inflammatory activity [28,40], and inflammation is one of the main pathways for neuronal death after ischemia in the gerbil hippocampus [41,42]. Overexpression of ROS induced by ischemia/reperfusion causes lipid peroxidation of polyunsaturated fatty acids in the neuronal membrane and disrupts the cell membrane [43].…”
Section: Discussionmentioning
confidence: 99%
“…The protocols were approved by the Institutional Animal Care and Use Committee (IACUC) of Seoul National University (SNU-170630-8-2). Forebrain ischemia was induced by the occlusion of both common carotid arteries in the neck region as described previously [41,61]. CVE (30 or 300 mg/kg) or vehicle (distilled water) was administered to gerbils using a feeding needle.…”
Section: Experimental Animalsmentioning
confidence: 99%